Association of triglyceride-glucose index with Helicobacter pylori infection in the 1999–2000 NHANES cross-sectional study - Wei Liu; Jie An; Cheng Jiao; Jun Guo; Lipu Zhang; Haifeng Jin; Guangchao Liu; Yao Zhang (Scientific Reports)
Abstract Helicobacter pylori (H. pylori) infection is linked to metabolic syndrome and insulin resistance, with the triglyceride-glucose (TyG) index serving as a reliable marker for the latter. This study investigates the association between the TyG index and H. pylori infection. The study utilized cross-sectional data from the National Health and Nutrition Examination Survey (NHANES) conducted between 1999 and 2000. Participants underwent serologic testing for H. pylori, and the TyG index was calculated from fasting laboratory measurements. Multivariate logistic regression and restricted cubic spline methods were used to assess the association and explore the dose–response relationship. The analysis included 2984 participants. Elevated TyG index values were associated with an increased likelihood of H. pylori infection. The risk of infection rose with higher TyG index quartiles, with the highest quartile showing the most significant increase (OR = 1.54, 95% CI: 1.15–2.07, P = 0.004). A linear relationship between the TyG index and H. pylori infection was demonstrated. The study findings indicate a significant positive association between the TyG index and H. pylori infection. This association highlights the importance of metabolic health in the context of H. pylori infection and suggests that further research is needed to explore the potential implications for health promotion strategies.